EXTENT OF USE OF THE NOVEL FABACEOUS HOST CENTROSEMA MOLLE BY HENOSEPILACHNA VIGINTIOCTOPUNCTATA (COLEOPTERA: COCCINELLIDAE) IN NUSA TENGGARA, INDONESIA - Naoyuki Fujiyama; Hideki Ueno; Sih Kahono; Sri Hartini; Kei W Matsubayashi; Shogo Kikuta; Haruo Katakura (BRIN Publishing (Penerbit BRIN), 2013)
-